Pengaruh Debat Calon Presiden dan Wakil Presiden Terhadap Perilaku Memilih Masyarakat Kelurahan Bahu pada Pemilu 2024 - Patasaka, Rini Indryati; Wansaga, Anita (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study is entitled "The Influence of the Marketing Mix (7P) on Consumer Purchase Decisions at POIN Café & Eatery in Bantul." The aim of this research is to determine the influence of the marketing mix (7P) on consumer purchase decisions at POIN Café & Eatery in Bantul. This research uses a quantitative approach with an associative method. The population consists of consumers who have purchased products at least once and are at least 17 years old. The sampling technique employed is purposive sampling, with a total of 100 respondents from POIN Café & Eatery consumers. Data analysis was performed using IBM SPSS 21 software. Data collection was carried out through questionnaires distributed directly to consumers of POIN Café & Eatery in Bantul. The results of this study indicate that the marketing mix (7P) variables have a positive and significant effect on purchase decisions, with partial test significance results < 0.05 for all seven independent variables. Simultaneously, the variables of product, price, place, promotion, people, process, and physical evidence have a significant effect on purchase decisions, as shown by the F-test result with a significance value of 0.000. Based on these findings, the marketing mix (7P) influences 85.3% of consumer purchase decisions.